2022
DOI: 10.1038/s41598-022-21413-y
|View full text |Cite
|
Sign up to set email alerts
|

Urban ecosystem drives genetic diversity in feral honey bee

Abstract: Urbanization can change biodiversity in both directions, positive and negative, and despite the rising global trend of urban beekeeping, little is known about the impact of urbanization on the genetic diversity of honey bees. We investigate how urbanization affects the genetic variability of feral and managed honey bee colonies that are spread throughout the entire city, even in highly urban areas, through genetic analysis of 82 worker bees. We found convincing evidence of high genetic differentiation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…These areas are typically composed of intermittent gardens, parks, green areas, and pockets of natural land giving insects an abundance of floral resources and nesting areas in comparison to agricultural land [123]. In contrast, urban areas with >50% or more IS do not foster biodiversity and are composed of abiotic, non-flowering surfaces such as sidewalks, car parks, buildings, etc., reducing overall floral resources and nesting habitats while increasing risk factors such as pollution, noise, and artificial light [120]. This is supported by Baldock et al's.…”
Section: Biopesticides In Urban Settingsmentioning
confidence: 77%
See 3 more Smart Citations
“…These areas are typically composed of intermittent gardens, parks, green areas, and pockets of natural land giving insects an abundance of floral resources and nesting areas in comparison to agricultural land [123]. In contrast, urban areas with >50% or more IS do not foster biodiversity and are composed of abiotic, non-flowering surfaces such as sidewalks, car parks, buildings, etc., reducing overall floral resources and nesting habitats while increasing risk factors such as pollution, noise, and artificial light [120]. This is supported by Baldock et al's.…”
Section: Biopesticides In Urban Settingsmentioning
confidence: 77%
“…Specifically, hymenopteran richness and abundance increase whilst those of dipterans, lepidopterans, and coleopterans typically see a small decrease [121]. The increase in hymenopteran richness and abundance is supported by (1) Patenković et al [120], who noticed significant survivorship and genetic variation amongst honey bees in urban settings; and (2) Samuelson et al [122], who observed an increase in colony size and food storage with a decrease in parasite load in Bombus terrestris [Hymenoptera: Apidae]. This is due to initial urban sprawl, the first step in urbanization, which creates areas with impervious surfaces (IS) of 50% or less [119].…”
Section: Biopesticides In Urban Settingsmentioning
confidence: 93%
See 2 more Smart Citations
“…This is challenging, though, because there aren’t many locations in Europe that are more than 15 km apart from an apiary ( Jensen et al, 2005 ). Even if in a particular area there are no colonies maintained by beekeepers in hives, a small feral population can still be present ( Kohl & Rutschmann, 2018 ; Patenković et al, 2022 ). In this situation, many breeders use instrumental insemination, which requires sophisticated equipment and qualified personnel.…”
Section: Introductionmentioning
confidence: 99%